Multifunctional combustion-synthesized nano-ceria: insights into ex-vivo goat cartilage tissue internalization and bioimaging - Hema Brindha Masanam; Ashwin Kumar Narasimhan; Ganapathy Krishnamurthi; Sruthi Ann Alex (Nano Express)
The internalization of cerium oxide nanoparticles (CeO _2−x NPs) in articular cartilage presents a novel approach to enhance imaging modalities for monitoring osteoarthritis (OA). This study introduces a bimodal cerium oxide-based nano-contrast agent synthesized via a one-step combustion method, aimed at addressing the limitations of earlier synthesis techniques that lacked dual functional properties for bioimaging. The combustion method produces high-yield nanoparticles that exhibit exceptional x-ray attenuation and redox properties, while also enhanced optical characteristics due to quench annealing processes. CeO _2−x NPs quench annealed at 700 °C (C7 NPs) were identified as effective bimodal contrast agents for cartilage imaging. Characterization of C7 NPs revealed distinct fluorescence emissions: greenish-blue ( λ _em = 381 nm) and yellowish-pink ( λ _em = 406 and 454 nm) under UV-C and UV-A excitation, indicating efficient down-conversion due to their unique size and energy band structures. The x-ray attenuation properties were assessed using tissue-mimicking phantoms, demonstrating values between 502 and 783 HU·ml/mg at low x-ray tube voltages, utilizing a custom-built benchtop micro-CT system. Ex vivo optical imaging conducted on goat articular cartilage tissues confirmed the effective internalization of C7 NPs (∼20 nm) within the transitional zone. This study is the first to report the internalization of combustion-synthesized CeO _2−x NPs in goat articular cartilage explants, underscoring their potential as bimodal agents for x-ray and optical imaging in articular cartilage tracking.